Severe osteomyelitis caused by Panton–Valentine leucocidin producing Staphylococcus aureus. (29th September 2015) - Alexander, E; Monda, M; Turnbull, T; Wynn, C; Fidler, K
Abstract : Aims: To raise awareness of serious infections due to Panton–Valentine leucocidin (PVL) toxin producing methicillin sensitive Staphylococcus aureus (MSSA) in children by presenting a case. Methods: A 10-year-old boy presented with a three day history of pain in the right shoulder, radiating down the arm, associated with fever and decreased range of movement. On examination he was febrile, tachcycardic and had localised erythema and tenderness over the right shoulder, with limited active and passive movement. Inflammatory markers were raised, but his neutrophils were normal. A diagnosis of septic arthritis was made and 5 ml of pus was washed out of his glenohumeral joint. His admission blood cultures grew MSSA but the intraoperative sample was culture negative. Despite intravenous flucloxacillin and a further joint washout, his inflammatory markers continued to rise and he developed respiratory distress requiring continuous positive airway pressure. An MRI scan revealed fluid under the periosteum, consistent with osteomyelitis of the humerus and a further surgical debridement was required. He was started on intravenous clindamycin in addition to high-dose intravenous flucloxacillin. Culture of the fluid from the right proximal humerus grew MSSA which was shown to carry genes encoding PVL. Despite aggressive ongoing antibiotic therapy, this child required six surgical debridements before he finally defervesced and his inflammatory markers began to settle. Results: PVL is a cytotoxin produced by S aureus that lyses leucocytes by creating pores on the cell surface. This may result in extensive tissue necrosis and severe infection. Currently, approximately 2% of S aureus isolates in the UK carry genes for PVL. The prevalence of this varies worldwide. Clinical presentations include skin infections (recurrent boils or cellulitis), septic arthritis/osteomyelitis, bacteremia, purpura fulminans and necrotising pneumonia. The latter often follows a flu-like illness. The mainstay of treatments is surgical drainage of affected areas and high doses of appropriate antibiotics. Prognosis depends on site of infection but mortality is high with necrotising pneumonia. Conclusion: This case highlights severe clinical infection with an emerging pathogen in the UK. Pneumonia caused by PVL producing staph aureus infections may increase during the expected flu pandemic this winter. Thus, it is important to raise awareness of this pathogen among clinicians